A Bis‐Binuclear NiII Complex with Easy and Hard Axes of Magnetization: Complementary Experimental and Theoretical Insights. Issue 3 (5th December 2017) - El‐Khatib, Fatima; Cahier, Benjamin; López‐Jordà, Maurici; Guillot, Régis; Rivière, Eric; Hafez, Hala; Saad, Zeinab; Guihéry, Nathalie; Mallah, Talal
Abstract : The preparation of a tetranuclear Ni II complex, constructed of two binuclear species each containing a macrocyclic cryptand‐like ligand and bridged by a nitrate anion, is reported. The metal ions within the binuclear species are hexacoordinate with different distorted environments. One nickel site, Ni1, has as a compressed octahedral geometry, whereas the other nickel site, Ni2, has a geometry closer to a square pyramid due to the presence of a long metal–ligand bond length. A study of the magnetic properties showed that the intradimer exchange coupling is larger than the interdimer coupling due to differences in the metal–ligand intra‐ and interdimer bond lengths, as confirmed by broken‐symmetry DFT calculations. Wave‐function‐based calculations allowed analysis of both the nature and the magnitude of the magnetic anisotropy of the two Ni sites. The Ni1 and Ni2 sites have, respectively, easy and hard axes of magnetization that are almost orthogonal. Magnetostructural correlations showed that the hard axis of magnetization of Ni2 is due to its geometry, which is closer to square‐pyramidal despite the hexacoordination. On the other hand, the easy axis of magnetization of the Ni1 site is a result of the compressed octahedral geometry. Abstract : The use of a cryptand ligand has allowed the design of an antiferromagnetically coupled nonsymmetrical Ni II binuclear complex with easy and hard magnetic axes, as demonstrated by complementary experimental and theoretical studies.